2012
DOI: 10.1158/1078-0432.ccr-11-3299
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Levels of TNF Receptor II Are Prognostic for Patients with Peripheral T-cell Non–Hodgkin Lymphoma

Abstract: Purpose: Peripheral T-cell non–Hodgkin lymphomas (T-NHL) represent a small but heterogeneous and clinically aggressive subset of NHLs with a poor outcome. Cytokines or their receptors might be associated with the clinical outcome of these lymphomas. Therefore, we tested whether gene variations and serum levels of soluble TNF receptor (TNFR)I (sTNFRI), sTNFRII, interleukin (IL)-10, or sIL-4R are predictive for treatment response in T-NHLs. Experimental Design: Peripheral blood DNA from 117 patien… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 54 publications
(73 reference statements)
0
28
0
1
Order By: Relevance
“…The levels of sTNF-R1 and sTNF-R2 in the vascular circulation are increased significantly with age and altered in obese individuals [24] and chronic inflammatory conditions and diseases [58] as well as several cancers [915]. Although correlations with the clinical stage, risk of progression, and the risk of developing certain cancers have been described [916] there is very little information on the levels of these soluble receptors in glioblastoma and their potential clinical relevance in GBM.…”
Section: Introductionmentioning
confidence: 99%
“…The levels of sTNF-R1 and sTNF-R2 in the vascular circulation are increased significantly with age and altered in obese individuals [24] and chronic inflammatory conditions and diseases [58] as well as several cancers [915]. Although correlations with the clinical stage, risk of progression, and the risk of developing certain cancers have been described [916] there is very little information on the levels of these soluble receptors in glioblastoma and their potential clinical relevance in GBM.…”
Section: Introductionmentioning
confidence: 99%
“…In previous years, it was reported that TNFR2 has important roles in the occurrence and progression of various types of tumor, including skin tumors, cholangiocarcinoma, myeloma, colorectal cancer and non-Hodgkin lymphoma (13)(14)(15)(16)(17). Jöhrer et al reported that high expression of TNFR2 promoted the metastasis of myeloma cells (15).…”
Section: Discussionmentioning
confidence: 99%
“…It was initially identified in hematopoietic cells and endothelial cells, and is involved in anti-inflammation, immune regulation, the repair of lung injury induced by lipopolysaccharide and the healing of bone fracture (10)(11)(12). The high expression of TNFR2 and its pro-progression roles have been previously reported in various types of tumor, including skin tumors, cholangiocarcinoma, myeloma, colorectal cancer and non-Hodgkin lymphoma (13)(14)(15)(16)(17). However, in BC, clinical studies about TNFR2 were mainly focused on sTNFR2 in the blood, and the clinical implication of TNFR2 in BC tissue remains limited (18,19).…”
Section: Introductionmentioning
confidence: 99%
“…For example, the T allele was significantly associated with systemic lupus erythematous [38], poor survival outcomes in non-small-cell lung cancers [39], and T cell non-Hodgkin's lymphoma [40]; however, this polymorphism was protective against oral carcinoma [41], which decreased the risk of colon cancer [42] and invasive pulmonary aspergillosis [43]. Kim et al [44] found out that the TNFRI −609G/T polymorphism was strongly associated with primary hepatocellular carcinoma and that the T allele repressed TNFRI expression.…”
Section: Discussionmentioning
confidence: 99%